Young and mature leaves of Azadirachta indica (neem) display different antidiabetic and antioxidative effects. Issue 1 (31st December 2023) - Mohammed, Abubakar; Kumar, Raushan; Ashfaq, Fauzia; Alsayegh, Abdulrahman A.; Al Areefy, Azza Abd El Hafiz; Khan, Mohammad Idreesh; Rizvi, Syed Ibrahim
ABSTRACT: Azadirachta indica (AI), popularly known as neem in India, has been used in the Indian Ayurvedic medicinal system for thousands of years in the management of varied ailments. The present study was undertaken to evaluate the antioxidant, antidiabetic, and anti-inflammatory activity of the crude ethanolic extract of the young and mature leaves of Azadirachta indica. We used FTIR to analyze the functional groups present in ethanolic AI extracts. Extracts of the young (YLE) and mature leaf (MLE) were administered to streptozotocin-induced diabetic rats. YLE and MLE reduced blood glucose, restored weight and maintained insulin and lipid levels, highlighting the antidiabetic action of both extracts. Significantly, the effect observed with YLE was greater as compared to MLE. The oxidative stress biomarkers were also normalized with respect to type 1 diabetic control. FTIR analysis showed several peaks present in the YLE 30 which were absent in the MLE. We found a decrease in the levels of Q3 inflammatory cytokines (IL-6 and TNF-alpha) in type 1 diabetic rats supplemented with YLE. YLE displays better anti-diabetic activity in comparison to MLE. Our results lend credence to the use of YLE of AI leaves as a useful supplementary candidate for future diabetes management therapy.